Molecular Interactions of Piperidinium Based Ionic Liquids with Water/Alcohol at Different Temperatures - Gangadhara Rao, G.V.; Babu, Shaik (Asian Journal of Chemistry, 2020)
In this experimental investigation, the thermodynamic fundamental parameters of density (ρ) and speed of sound (U) were calibrated for aqueous solution/alcoholic (1-propanol and 2-propanol) solutions of piperidinium based ionic liquids of 1-butyl-1-methylpiperidinium tetrafluoroborate (BMPiBF4) in various concentrations within temperatures from 303.15 to 313.15 K. From these experimental determined values, various thermodynamic acoustic parameters of excess molar isentropic compressibility (KEs,m), excess molar volume (VEm) are expressed in specific and non-specific molecular interactions. Moreover, calibration of the partial molar volume′s and partial isentropic compressibility′s of both components shows strong interaction in BMPiBF4 + 2-proponol combination than any other executed binary composites. In addition to this, the FTIR characteristic spectrum of all combinations at different concentrations gives the more promising features such as interaction behaviour that helps our analysis to guide the interactions of individual bonds.